Narasi Populer Indonesia Pasca Reformasi: Sebuah Kajian Psikokultural - Siti Aliyuna Pratisti; Deasy Silvya Sari; Taufik Hidayat (Umbara, 2019)
Studies on Indonesian politics of identity after the reform present discussions on conflict-prone identities. Among them are conflicts based on multiculturalism; such as ethnicity, religion, and the relationship between minorities and majorities. Drawing at the current popular narratives in the written material and movies, this article aims at explaining identity-based conflicts in Indonesia, in particular a group trauma related to identity conflicts in Indonesia. Using psychocultural narrative theory, this article examining various cultural elements of the narratives, such as language, religion, social practice, and music and how it reflects the identity and conflict narrative in Indonesia after the reform. This article suggests that the current popular narratives offers the nuances of 1) bringing the Chinese-Indonesian identity back to the Indonesian political space, 2) presenting a new narratives of the 1965 tragedy using the perspective of the victims, and 3) presenting a narratives on religion based-conflicts.